IDENTIFICATION OF SECONDARY METABOLITE COMPOUNDS IN TUNICATE (Polycarpa aurata) ASSOCIATED BACTERIA - Sheila Raisa; Astika Widy Utomo; Rebriarina Hapsari; Endang Mahati (Jurnal Kedokteran Diponegoro, 2021)
Background: Marine biodiversity in the last few decades has been explored and utilized as marine natural products. The secondary metabolites produced by marine organisms are utilized by humans in various aspects of life. One of the main source of secondary metabolites is marine invertebrates, such as tunicate. Several previous studies have shown that many metabolites have been identified in the last 40 years.